Various Layers in Social Psychology - Mehrad, Aida; Cordic, Sarah; Crecelius, Grace; Procise, Woods; Wagner, Kylie (Jurnal Psikologi Integratif, 2024)
Understanding humans through social influence is always needed. Through an analysis of specific topics of social psychology, a bridge between issues can be created. This research aims to understand the various layers in social psychology using secondary data. The methodology used in this study is qualitative research, particularly literature review. The subject of this study is some literatures in databases, and other scholarly articles to use as supporting evidence for this work about the study of social psychology. The results provide understanding of layers on social psychology including how individuals interact and function in the day-to-day lives. Human can learn how to better recognize the information process happening in their brains and how to manipulate it in different social situations. The depth of how human relate to each other, and their surroundings is seen through social psychology's "social" aspect. Individuals thoughts, feelings, and behaviors are unique and influenced by social norms' real or imagined presence. This study has theoretical implication on how social psychology has layers to explain how human interact in social context.   Pemahaman tentang manusia melalui pengaruh sosial selalu dibutuhkan. Melalui analisis topik-topik tertentu psikologi sosial, jembatan antar permasalahan dapat diciptakan. Penelitian ini bertujuan untuk memahami berbagai lapisan dalam psikologi sosial dengan menggunakan data sekunder. Metodologi yang digunakan dalam penelitian ini adalah penelitian kualitatif khususnya tinjauan pustaka. Subyek penelitian ini adalah beberapa literatur dalam database, dan artikel ilmiah lainnya yang digunakan sebagai bukti pendukung karya tentang studi psikologi sosial ini. Hasilnya memberikan pemahaman tentang lapisan psikologi sosial termasuk bagaimana individu berinteraksi dan berfungsi dalam kehidupan sehari-hari. Manusia dapat belajar bagaimana mengenali dengan lebih baik proses informasi yang terjadi di otaknya dan bagaimana memanipulasinya dalam berbagai situasi sosial. Kedalaman hubungan manusia satu sama lain, dan lingkungannya dilihat melalui aspek “sosial” psikologi sosial. Pikiran, perasaan, dan perilaku individu bersifat unik dan dipengaruhi oleh kehadiran norma-norma sosial yang nyata atau yang dibayangkan. Kajian ini mempunyai implikasi teoritis mengenai bagaimana psikologi sosial mempunyai lapisan-lapisan untuk menjelaskan bagaimana manusia berinteraksi dalam konteks sosial.